Impact of tumor microenvironment on efficacy of anti-CD19 CAR T cell therapy or chemotherapy and transplant in large B cell lymphoma - Locke, Frederick; Filosto, Simone; Chou, Justin; Vardhanabhuti, Saran; Perbost, Regis; Dreger, Peter; Hill, Brian T.; Lee, Catherine; Zinzani, Pier L.; Kröger, Nicolaus; López-Guillermo, Armando; Greinix, Hildegard; et al. (Nature medicine, 2024)
The phase 3 ZUMA-7 trial in second-line large B cell lymphoma demonstrated superiority of anti-CD19 CAR T cell therapy (axicabtagene ciloleucel (axi-cel)) over standard of care (SOC; salvage chemotherapy followed by hematopoietic transplantation) (NCT03391466). Here, we present a prespecified exploratory analysis examining the association between pretreatment tumor characteristics and the efficacy of axi-cel versus SOC. B cell gene expression signature (GES) and CD19 expression associated significantly with improved event-free survival for axi-cel (P = 0.0002 for B cell GES; P = 0.0165 for CD19 expression) but not SOC (P = 0.9374 for B cell GES; P = 0.5526 for CD19 expression). Axi-cel showed superior event-free survival over SOC irrespective of B cell GES and CD19 expression (P = 8.56 × 10-9 for B cell GES high; P = 0.0019 for B cell GES low; P = 3.85 × 10-9 for CD19 gene high; P = 0.0017 for CD19 gene low). Low CD19 expression in malignant cells correlated with a tumor GES consisting of immune-suppressive stromal and myeloid genes, highlighting the inter-relation between malignant cell features and immune contexture substantially impacting axi-cel outcomes. Tumor burden, lactate dehydrogenase and cell-of-origin impacted SOC more than axi-cel outcomes. T cell activation and B cell GES, which are associated with improved axi-cel outcome, decreased with increasing lines of therapy. These data highlight differences in resistance mechanisms to axi-cel and SOC and support earlier intervention with axi-cel.